Optimalisasi Load Balancing Menggunakan Metode NDLC untuk Meningkatkan Kualitas Layanan Jaringan Internet - Isro, Aditya Bani; Zy, Ahmad Turmudi; Andika, Sophian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research focuses on the main problem of internet network instability that is often disconnected and the low quality of network services characterized by slow access speeds, high latency, and fluctuations in network performance at SMK Al-Manar Islamic School. This instability causes disruptions in the teaching and learning process, such as slow access to educational websites, difficulty in accessing online materials, and disruption in the use of internet-based applications. The purpose of this research is to improve the quality of network services through the implementation of load balancing using Mikrotik router. The method used is Network Development Life Cycle (NDLC), which includes the stages of analysis, design, simulation, implementation, monitoring, and management. Data was collected through literature study, field study, and observation using Wireshark to measure QoS parameters such as throughput, packet loss, delay, and jitter before and after the implementation of load balancing. The results showed that the implementation of load balancing successfully increased throughput from 14215.591 kbps to 46460.8675 kbps, reduced delay from 135 ms to 7 ms, and decreased jitter from 135.615 ms to 73.293 ms. The packet loss value remains 0%, both before and after implementation. In conclusion, the implementation of load balancing using Mikrotik router has successfully improved the quality of internet network services at SMK Al-Manar Islamic School, making it faster, more stable and efficient in accordance with TIPHON standards. It is recommended that schools continue to monitor and manage the network regularly to maintain optimal performance.